Observasi Interaksi Sosial dan Aktivitas Fisik pada Ruang Hijau di Masjid - Setiawan, Afifah Ghifari Putri; Sunarya, Wendy (Universitas Medan Area, 2025)
The relationship between green spaces and humans has long been recognized as one of the important aspects of life, especially in urban contexts. In urban environments, green spaces are often found in public areas, serving as places for recreation, sports, and social interaction, as well as helping to reduce pollution and noise. One common form of public space in Indonesia is the mosque, which not only functions as a place of worship but also plays an important role as a center for social, cultural, and educational activities. If a mosque provides green space, it can positively impact urban well-being. The aim of this research is to understand the role of green spaces in mosques in enhancing social interaction and human physical activity. The literature study method was used to collect and analyze previously published information related to the topic. Another method used is field observation with a behavior mapping approach to record and analyze social interactions and physical activities occurring in the green spaces of three mosques with different green space conditions over a certain period of time. The results of the study show that there are longer durations of social interactions and physical activities such as communicating, relaxing, playing, and worshiping in mosques with green spaces compared to those without green spaces. Thus, it is concluded that green spaces in mosques can be optimized as places for social interaction and physical activity, providing numerous benefits to the community, including improved physical and mental health and an overall enhanced quality of life.